2009
DOI: 10.1007/s12310-009-9016-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Integrity of Intervention Implementation: Critical Factors and Future Directions

Abstract: The series of articles on assessing integrity of intervention implementation advance the field by articulating three interrelated themes including that intervention integrity is a complex, multifaceted construct; integrity should be fostered and monitored in a proactive fashion; and multiple methods and respondents are necessary to comprehensively assess intervention integrity. These themes are discussed with a view towards important directions for future research in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
6
0
3
Order By: Relevance
“…These findings suggest that low adherence compromises positive student outcomes, leading to the assumption that more integrity is better (DuPaul, 2009). However, this assumption has yet to be tested empirically.…”
Section: Intervention Integritymentioning
confidence: 99%
“…These findings suggest that low adherence compromises positive student outcomes, leading to the assumption that more integrity is better (DuPaul, 2009). However, this assumption has yet to be tested empirically.…”
Section: Intervention Integritymentioning
confidence: 99%
“…Program fidelity is positively associated with program effectiveness (Leff, Hoffman, & Gullan, 2009), and, when programs don't work, information on program fidelity is key to distinguishing between an ineffective program and a poorly implemented one (Gresham, Gansle, & Noell, 1993). However, information regarding fidelity, or intervention integrity (Leff et al, 2009), is rarely reported and even less likely to be a direct focus of study (DuPaul, 2009). For example, in their review of 249 violence prevention programs, Wilson & Lipsey (2007) found that the majority of studies (65%) did not contain information on implementation fidelity.…”
Section: Fostering Resilient Outcomes Among Youth Exposed To Chronic mentioning
confidence: 99%
“…There is an emerging research base outlining ways to improve both the measurement and collection of fidelity data (Leff et al, 2009). First, there is a need to broaden the traditional conceptualization of program fidelity beyond the degree to which the program was delivered as intended to include how well the program was delivered (quality) and how the program was received (child/parent perception; DuPaul, 2009; Power et al, 2009). Second, program developers and trainers need to be more proactive in fostering fidelity monitoring.…”
Section: Fostering Resilient Outcomes Among Youth Exposed To Chronic mentioning
confidence: 99%
“…Sin embargo, saber qué intervenciones funcionan es solo una parte de la ecuación, pues también es fundamental entender cómo implementarlas, para obtener los beneficios que prometen. Este punto es crítico en el contexto dinámico y heterogéneo de las escuelas, donde no es difícil que una intervención, que ha demostrado ser eficaz, no genere los resultados deseados debido a la falta de fidelidad de la implementación (FI) (Dupaul, 2009;Durlak y DuPre, 2008;Sarno et al, 2014).…”
Section: Effects Of Implementation Fidelity Of the Results Of A Preveunclassified
“…La mayoría de los investigadores están de acuerdo en que la FI se trata de un constructo multidimensional (Dane y Schneider, 1998;Dupaul, 2009;Hagermoser-Sanetti y Kratochwill, 2009;Sarno et al, 2014) y multinivel (Zvoch, 2012) que involucra aspectos tanto del contexto del implementador como del intervenido. Respecto al implementador, la FI incluye: a) la adherencia, que se refiere al grado en que el interventor cumple o se apega a los componentes prácticos especificados (Schulte et al, 2009), y b) la calidad de la intervención, que se refiere al grado en que el interventor ejecuta las acciones de manera hábil, entusiasta y comprometida (Dane y Schneider, 1998;Low, van Ryzin, Brown, Smith y Haggerty, 2014).…”
Section: Fidelidad De La Implementaciónunclassified